An adaptive neuro-fuzzy inference system employed cuk converter for PV applications - Priyadarshi N.; Padmanaban S.; Holm-Nielsen J.B.; Ramachandaramurthy V.K.; Bhaskar M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adaptive control systems; Computer circuits; DC-DC converters; Fuzzy logic; Fuzzy neural networks; Fuzzy systems; Inference engines; Power electronics; Solar radiation; Adaptive neuro-fuzzy inference system; D-space; Fuzzy logic control; Optimal power points; Photovoltaic; Fuzzy inference